CuCl2·2H2O/TBHP mediated synthesis of β-enaminones via coupling reaction of vinyl azides with aldehydes. Issue 9 (16th February 2022) - Zhang, Yaohong; Luo, Mengqiang; Zhang, Yichan; Cheng, Kai; Li, Yong; Qi, Chenze; Shen, Runpu; Wang, Hai
Abstract : A facile and efficient oxidative functionalization of vinyl azides with aldehydes furnishing a diverse array of β-acylated enaminones was developed. Abstract : A facile and efficient oxidative functionalization of vinyl azides with aldehydes furnishing a diverse array of β-acylated enaminones was developed. The cross coupling was accomplished in the presence of CuCl2 ·2H2 O/TBHP and produced the desired β-acylated enaminones in a ( Z )-stereo-selective and atom-economic manner, which make this protocol particularly attractive. In the transformation, the new C–C and C–N bonds were formed via a one-pot strategy including the process of radical addition and recombination.